2017
DOI: 10.1093/occmed/kqx047
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Scottish military veterans: a 30-year retrospective cohort study

Abstract: Background: Although reassuring data on suicide risk in UK veterans of the 1982 Falklands

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…We reported antecedent diagnoses rather than causes of death as we only had a single ICD code for each individual cause of death, which may not have captured underlying conditions. We have reported on mortality and case-fatality in specific conditions elsewhere [6,21,29]. Smoking-related diseases were the commonest antecedent diagnoses in veterans who died (Table 2), affecting 46% of veterans compared with 39% of nonveterans, demonstrating the importance of lifestyle factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported antecedent diagnoses rather than causes of death as we only had a single ICD code for each individual cause of death, which may not have captured underlying conditions. We have reported on mortality and case-fatality in specific conditions elsewhere [6,21,29]. Smoking-related diseases were the commonest antecedent diagnoses in veterans who died (Table 2), affecting 46% of veterans compared with 39% of nonveterans, demonstrating the importance of lifestyle factors.…”
Section: Resultsmentioning
confidence: 99%
“…We examined health outcomes and mortality from 1 January 1981 (or date of leaving the Service for veterans, if later) to the date of death or 31 December 2012. We have previously described the characteristics of the study cohort and the methodology [6,21]. Approval for the study was granted by the We used Cox proportional hazard analysis to calculate hazard ratios (HRs) for death in veterans compared with people with no record of service, using age as the timedependent variable, age at death as the failure time, and age at the end of follow-up (if no death) as the censor time.…”
Section: Methodsmentioning
confidence: 99%
“…There are two distinct patterns of risk, in the early 20s for the youngest veterans who left service early, and in middle age. We had no clinical details of the cases and were, therefore, unable to distinguish between non-suicidal self-harm and failed suicide; however, it seems likely that the younger ESL cases largely represent the former whereas those presenting in middle age may be more likely to represent failed suicide attempts, based on patterns of deliberate self-harm reported in other studies [20], on the pattern of suicide in veterans that we have previously reported [7], and on the reported occurrence of prior self-harm in relation to completed suicide that we have found in this study. Although deliberate self-harm and parasuicide (attempted suicide) are frequently considered to lie on the same spectrum, there is good evidence that the two have different underlying psychopathology and should be considered separately, as now recognised by the separate DSM-5 classifications of 'non-suicidal self-injury' and 'suicidal behavior' [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…We used Scottish linked health records (which cover all individuals registered with NHS Scotland) and mortality data to compare longterm risk of suicide and major self-harm in veterans and non-veterans, obtaining a single retrospective data download as at 31 December 2012. The study cohort and methods have been described in detail previously [12], and the findings in respect of suicide have recently been published [7]. This paper examines non-fatal self-harm leading to hospitalisation, encompassing both non-suicidal intent and failed suicide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation